Review of deep fluids in sedimentary basins and their influence on resources, with a focus on oil and geothermal exploitation - Lu, Jia; Li, Chuanming; Wang, Maoyun; Zhang, Chengju (Frontiers in Earth Science, 2023)
Deep fluid activity is widespread in large oil-gas basins around the world. Deep fluids, as the links between internal and external factors of a basin, run in the way of organic-inorganic interactions through the oil-gas formation and aggregation. Herein, the identification characteristics of deep fluids in sedimentary basins as well as their influence on oil-gas reservoir formation and geothermal resource are summarized. The deep fluids of sedimentary basins are identified from three aspects, including mineral composition, fluid inclusions, and geochemical characteristics. The effects of deep fluid activities on oil-gas reservoir formation are manifested in two key aspects of matter and energy. As for the matter effects, deep fluids can improve the primary productivity of sedimentary basins and carry abundant inorganic hydrogen, which contributes to improving the hydrocarbon productivity through hydrogenation. As for the energy effects, the heat energy of deep fluids can promote the mature evolution from organic matter to oil and gas. During this process, the heating of deep fluids will cause the oil-generation window depth of the hydrocarbon source rocks to become thinner, and it will also generate very high pressure, which will promote the discharge of abundant hydrocarbons formed by the hydrocarbon source rocks. Furthermore, deep fluids can directly form volcanic rock oil-gas reservoirs. And another manifestation of deep fluid energy is geothermal. And the thermal energy of deep fluids can directly form hot dry rocks, which is the most important existing form of geothermal resources. The geological exploration of hot dry rocks should be supported by further geochemical and geophysical research.